Determinants of Hospital Variation in Cardiac Rehabilitation Enrollment During Coronary Artery Disease Episodes of Care. Issue 2 (February 2021) - Thompson, Michael P.; Yaser, Jessica M.; Hou, Hechuan; Syrjamaki, John D.; DeLucia, Alphonse; Likosky, Donald S.; Keteyian, Steven J.; Prager, Richard L.; Gurm, Hitinder S.; Sukul, Devraj
Abstract : Background: Cardiac rehabilitation (CR) is associated with improved outcomes for patients with coronary artery disease (CAD). However, CR enrollment remains low and there is a dearth of real-world data on hospital-level variation in CR enrollment. We sought to explore determinants of hospital variability in CR enrollment during CAD episodes of care: medical management of acute myocardial infarction (AMI-MM), percutaneous coronary intervention (PCI), and coronary artery bypass grafting (CABG). Methods: A cohort of 71 703 CAD episodes of care were identified from 33 hospitals in the Michigan Value Collaborative statewide multipayer registry (2015 to 2018). CR enrollment was defined using professional and facility claims and compared across treatment strategies: AMI-MM (n=18 678), PCI (n=41 986), and CABG (n=11 039). Hierarchical logistic regression was used to estimate effects of predictors and hospital risk-adjusted rates of CR enrollment. Results: Overall, 20 613 (28.8%) patients enrolled in CR, with significant differences by treatment strategy: AMI-MM=13.4%, PCI=29.0%, CABG=53.8% ( P <0.001). There were significant differences in CR enrollment across age groups, comorbidity status, and payer status. At the hospital-level, there was over 5-fold variation in hospital risk-adjusted CR enrollment rates (9.8%–51.6%). Hospital-level CR enrollment rates were highly correlated across treatment strategy, with the strongest correlation between AMI-MM versus PCI (R 2 =0.72), followed by PCI versus CABG (R 2 =0.51) and AMI-MM versus CABG (R 2 =0.46, all P <0.001). Conclusions: Substantial variation exists in CR enrollment during CAD episodes of care across hospitals. However, within-hospital CR enrollment rates were significantly correlated across all treatment strategies. These findings suggest that CR enrollment during CAD episodes of care is the product of hospital-specific rather than treatment-specific practice patterns. Abstract : Supplemental Digital Content is available in the text.